Effect of ginger extract and sugar level in the sensorial quality and acceptability of Sinaging processed from swamp taro (Cyrtosperma chamissonis) - Bandalan, Melogen B.; Morbos, Clarita E.; Gonzaga, Jenalyn M.; Cabugawan, Eliza C.; Lombrio, Amalia Paraluman B. (Annals of Tropical Research, 2021)
This study aimed to evaluate the sensory quality and acceptability of Sinaging as affected by the different levels of ginger extract and calamay sugar, obtain the optimum combination of ginger extract and calamay sugar, and determine the cost of producing Sinaging. A 3×3 Full Factorial experiment in Completely Randomized Design was employed. Three levels of ginger extract (2, 4, 6 %w/w) and sugar levels (20, 25, 30 %w/w) were the variables considered. Sensory evaluation using quality scoring in combination with the 9-point Hedonic scale was carried out. The results were subjected to statistical analysis using Statistica 8.0 software and Statistical Analytical Software version 9 (SAS 2008). Results revealed that the different levels of sugar and ginger extract significantly affected linearly the flavor, taste, and general acceptability of Sinaging. No significant effect was observed on its color, aroma, texture, and aftertaste. The mean acceptability rating of the different treatments ranged from 7.15 to 7.41 which corresponds to ‘like moderately’ in the 9-point Hedonic scale. The optimum combination was at 4.05% and 28.75% ginger extract and sugar, respectively. The production cost of the optimum formulation was 8.34 pesos per piece weighing 75g of Sinaging.